Binder aqueous solution for lithium ion battery, negative electrode slurry for lithium ion battery, negative electrode for lithium ion battery, and lithium ion battery
By using an aqueous binder solution composed of a water-soluble polymer and a hydrolyzed partial condensate of a trialkoxysilane containing amino groups, the problem of reducing the softness of the electrode during the crosslinking process of the adhesive for lithium-ion batteries is solved, and high dispersion stability and discharge capacity maintenance are improved.
Patent Information
- Application Number
- CN202110333132.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-03-30
- Filing Date
- 2021-03-29
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-03-29
AI Technical Summary
The existing binder aqueous solution for lithium-ion batteries causes the electrode flexibility to decrease during the crosslinking process, and the dispersion stability and storage stability of the slurry are insufficient, which affects the discharge capacity maintenance rate.
The aqueous binder solution consisting of a water-soluble polymer (A) and a hydrolyzed partial condensate of trialkoxysilane containing amino groups is used to combine hydroxyalkyl (meth)acrylate with hydroxyalkyl (meth)acrylate having hydroxyalkyl groups having 2 to 4 carbon atoms, and the composition and structure of the binder are adjusted to improve the softness of the electrode and the dispersion stability of the slurry.
The excellent softness and high dispersion stability of the negative electrode of the lithium-ion battery are achieved, and the discharge capacity maintenance rate of the lithium-ion battery is improved.
Smart Images

Figure BDA0002997049910000071 
Figure BDA0002997049910000151 
Figure BDA0002997049910000291
Abstract
Description
Technical Field
[0001] The present disclosure relates to a binder aqueous solution for a lithium ion battery, a negative electrode slurry for a lithium ion battery, a negative electrode for a lithium ion battery, and a lithium ion battery. Background Art
[0002] Lithium-ion batteries are small, lightweight, have high energy density, and can be repeatedly charged and discharged, and have been used in a wide range of applications. Therefore, in recent years, research has been conducted on improving battery components such as electrodes in order to further improve the performance of lithium-ion batteries.
[0003] The positive and negative electrodes of lithium-ion batteries are manufactured by the following method: a slurry formed by dispersing an electrode active material and a binder resin in a solvent is applied to both sides of a current collector (such as a metal foil), the solvent is dried and removed to form an electrode layer, and then the electrode layer is compression-molded using a roller press or the like.
[0004] In recent years, various electrode active materials have been proposed in lithium ion battery electrodes from the viewpoint of increasing battery capacity. However, depending on the electrode active material, expansion and contraction are likely to occur with charge and discharge. Therefore, the lithium ion battery electrode that is likely to expand and contract with charge and discharge changes in volume compared to the initial stage due to repeated charge and discharge, and the electrical characteristics such as the cycle characteristics of the lithium ion battery using the lithium ion battery electrode are likely to be reduced.
[0005] Therefore, in this field, attempts are being made to use binder resins to solve the above technical problems. For example, it is proposed to obtain good charge and discharge characteristics by using polyacrylamide as a binder of a water-soluble resin (Patent Documents 1 and 2). In addition, for the expansion and contraction accompanying the charge and discharge of the active material, it is proposed to suppress the expansion by adding a crosslinking agent to the particulate resin as a binder resin (Patent Document 3). The crosslinking agent usually undergoes a crosslinking reaction in the drying step after applying the slurry composition to the collector, and forms crosslinks between particles of the particulate resin.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2015-118908
[0009] Patent Document 2: Japanese Patent Application Publication No. 2015-106488
[0010] Patent Document 3: International Publication No. 2015 / 098507 Summary of the invention
[0011] Technical problem to be solved by the invention
[0012] However, when a cross-linking agent is used for cross-linking, the flexibility of the binder resin is reduced, and as a result, the problem of reducing the flexibility of the electrode may occur. In addition, in the prior art, the dispersion stability and storage stability of the slurry are insufficient. In addition, the binder is also required to give a good discharge capacity retention rate to the lithium ion battery.
[0013] Therefore, one of the problems to be solved by the present invention is to provide a binder aqueous solution for lithium ion batteries that can provide a good discharge capacity retention rate for lithium ion batteries, good flexibility for negative electrodes, and good dispersion stability and storage stability for slurry.
[0014] Another object is to provide a negative electrode slurry for a lithium ion battery that provides a good discharge capacity retention rate to a lithium ion battery, provides good flexibility to a negative electrode, and has good dispersion stability and storage stability.
[0015] The present inventors have conducted intensive studies and have found that the above-mentioned problems can be solved.
[0016] The following items are provided according to the present disclosure.
[0017] (Item 1)
[0018] A binder aqueous solution for lithium ion batteries, the binder aqueous solution for lithium ion batteries having a pH of 5 or more and comprising:
[0019] A water-soluble polymer (A) which is a polymer of a monomer group containing 15 mol % to 99.9 mol % of an unsaturated carboxylic acid or an inorganic salt thereof relative to 100 mol % of the monomer group and has a glass transition temperature of 110° C. or lower; and
[0020] A hydrolyzed partial condensate of an amino group-containing trialkoxysilane (B).
[0021] (Item 2)
[0022] The aqueous binder solution for lithium ion batteries as described in the above item contains 15 mol % to 60 mol % of a hydroxyalkyl (meth)acrylate having a hydroxyalkyl group having 2 to 4 carbon atoms, based on 100 mol % of the monomer group.
[0023] (Item 3)
[0024] In the aqueous binder solution for lithium ion batteries as described in any one of the above items, the molar ratio of the amino group of the hydrolyzed partial condensate of the amino group-containing trialkoxysilane (B) to the carboxyl group of the water-soluble polymer (A) (amino group / carboxyl group) is 0.05 or more.
[0025] (Item 4)
[0026] A negative electrode slurry for a lithium ion battery, the negative electrode slurry for a lithium ion battery comprising:
[0027] A water-soluble polymer (A), wherein the water-soluble polymer (A) is a polymer of a monomer group containing 15 mol% to 99.9 mol% of an unsaturated carboxylic acid or an inorganic salt thereof relative to 100 mol% of the monomer group, and has a glass transition temperature of 110°C or less;
[0028] A hydrolyzed partial condensate of an amino group-containing trialkoxysilane (B);
[0029] A negative electrode active material (C); and
[0030] A conductive carbon additive (D) having a zeta potential of 0 mV or more at pH 5 to 7.
[0031] (Item 5)
[0032] A negative electrode for a lithium ion battery is obtained by applying the negative electrode slurry for a lithium ion battery as described in the above item on a current collector and drying and solidifying it.
[0033] (Item 6)
[0034] A lithium ion battery comprising the negative electrode for a lithium ion battery as described in the above item.
[0035] In the present disclosure, in addition to the combinations explicitly described, one or more of the above features may be provided in further combinations.
[0036] Beneficial Effects
[0037] The binder aqueous solution for lithium ion batteries described in this embodiment can give excellent dispersion stability and storage stability to the negative electrode slurry for lithium ion batteries. In addition, the negative electrode slurry for lithium ion batteries described in this embodiment has excellent dispersion stability and storage stability. Furthermore, the negative electrode described in this embodiment has excellent flexibility. Moreover, the lithium ion battery described in this embodiment has excellent discharge capacity retention rate. DETAILED DESCRIPTION
[0038] In the entire scope of the present disclosure, the range of the numerical values of each physical property value, content, etc. can be appropriately set (for example, selected from the upper and lower limit values described in each of the following items). Specifically, with respect to the numerical value α, when A4, A3, A2, A1 (A4>A3>A2>A1) and the like are exemplified as the upper and lower limits of the numerical value α, the range of the numerical value α is exemplified as less than A4, less than A3, less than A2, more than A1, more than A2, more than A3, A1-A2, A1-A3, A1-A4, A2-A3, A2-A4, A3-A4, etc.
[0039] [Aqueous binder solution for lithium-ion batteries: also called aqueous solution]
[0040] The present disclosure provides an aqueous binder solution for lithium ion batteries, wherein the pH of the aqueous binder solution for lithium ion batteries is 5 or more and the aqueous binder solution comprises:
[0041] A water-soluble polymer (A) which is a polymer of a monomer group containing 15 mol % to 99.9 mol % of an unsaturated carboxylic acid or an inorganic salt thereof relative to 100 mol % of the monomer group and has a glass transition temperature of 110° C. or lower; and
[0042] A hydrolyzed partial condensate of an amino group-containing trialkoxysilane (B).
[0043] <Water-soluble polymer: also referred to as component (A)>
[0044] The component (A) may be used alone or in combination of two or more.
[0045] In the present disclosure, "water-soluble" means that when 0.5 g of the compound is dissolved in 100 g of water at 25°C, the insoluble component is less than 0.5% by mass (less than 2.5 mg).
[0046] When the component (A) is not water-soluble, it does not form an aqueous solution because it is insoluble in water. As a result, the component (A) does not contribute to the dispersion of the slurry. In addition, the slurry cannot be given the viscosity required for coating on the collector.
[0047] When 0.5 g of the component (A) is dissolved in 100 g of water, the insoluble content of the component (A) is, for example, less than 0.5 mass %, less than 0.4 mass %, less than 0.3 mass %, less than 0.2 mass %, less than 0.1 mass %, or 0 mass %.
[0048] In the present disclosure, “(meth)acrylic acid” means “at least one selected from the group consisting of acrylic acid and methacrylic acid”. Similarly, “(meth)acrylate” means “at least one selected from the group consisting of acrylate and methacrylate”. Furthermore, “(meth)acryloyl” means “at least one selected from the group consisting of acryloyl and methacryloyl”.
[0049] (unsaturated carboxylic acid or its inorganic salt)
[0050] The unsaturated carboxylic acid or its inorganic salt may be used alone or in combination of two or more.
[0051] Examples of unsaturated carboxylic acids include (meth)acrylic acid, crotonic acid, maleic acid, fumaric acid, itaconic acid, etc. Among them, when (meth)acrylic acid, especially acrylic acid, is used, a binder having high interaction with the electrode active material and the conductive carbon auxiliary agent and good slurry dispersibility can be provided.
[0052] Examples of the inorganic salt include alkali metal salts, alkaline earth metal salts, etc. In the present disclosure, an inorganic salt of an organic substance (e.g., an inorganic salt of one or more unsaturated acids selected from the group consisting of unsaturated carboxylic acids and unsaturated sulfonic acids, or an inorganic salt of component (A), etc.) refers to a salt whose cation portion is a metal cation.
[0053] Examples of the alkali metal include lithium, sodium, and potassium.
[0054] Examples of the alkaline earth metal include magnesium and calcium.
[0055] The upper and lower limits of the content of the unsaturated carboxylic acid or its inorganic salt relative to 100 mol% of the monomer group are exemplified by 99.9 mol%, 99 mol%, 95 mol%, 90 mol%, 89.95 mol%, 85 mol%, 80 mol%, 75 mol%, 70 mol%, 65 mol%, 60 mol%, 59.95 mol%, 55 mol%, 50 mol%, 45 mol%, 40 mol%, 36.7 mol%, 35 mol%, 30 mol%, 25 mol%, 20 mol%, 15 mol%, etc. In one embodiment, the above content is preferably 15 mol% to 99.9 mol%.
[0056] The upper and lower limits of the content of the unsaturated carboxylic acid or its inorganic salt relative to 100 mass % of the monomer group are exemplified as 99.9 mass %, 99 mass %, 95 mass %, 90 mass %, 85 mass %, 80 mass %, 75 mass %, 70 mass %, 65 mass %, 60 mass %, 55 mass %, 50 mass %, 45 mass %, 40 mass %, 36.7 mass %, 35 mass %, 30 mass %, 25 mass %, 20 mass %, 15 mass %, 10 mass %, 5 mass %, etc. In one embodiment, the above content is preferably 5 mass % to 99.9 mass %.
[0057] (Hydroxyalkyl (meth)acrylate having a hydroxyalkyl group having 2 to 4 carbon atoms)
[0058] In one embodiment, the monomer group may include a hydroxyalkyl(meth)acrylate having a hydroxyalkyl group having 2 to 4 carbon atoms. The hydroxyalkyl(meth)acrylate having a hydroxyalkyl group having 2 to 4 carbon atoms may be used alone or in combination of two or more.
[0059] In the present disclosure, a "hydroxyalkyl group having 2 to 4 carbon atoms" refers to a group in which one of the hydrogen atoms constituting an alkyl group having 2 to 4 carbon atoms is substituted with a hydroxy group.
[0060] Examples of the hydroxyalkyl (meth)acrylate having a hydroxyalkyl group having 2 to 4 carbon atoms include 1-hydroxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 1-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxy-1-methylethyl (meth)acrylate, 1-hydroxy-2-methylethyl (meth)acrylate, 1-hydroxybutyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxybutyl (meth)acrylate, and 2-hydroxybutyl (meth)acrylate. 4-Hydroxybutyl acrylate, 1-hydroxy-1-methyl-propyl (meth)acrylate, 2-hydroxy-1-methyl-propyl (meth)acrylate, 3-hydroxy-1-methyl-propyl (meth)acrylate, 1-ethyl-2-hydroxyethyl (meth)acrylate, 1-hydroxy-2-methyl-propyl (meth)acrylate, 2-hydroxy-2-methyl-propyl (meth)acrylate, 3-hydroxy-2-methyl-propyl (meth)acrylate, 1,1-dimethyl-2-hydroxyethyl (meth)acrylate, and the like.
[0061] Among them, when 2-hydroxyethyl (meth)acrylate, particularly 2-hydroxyethyl acrylate, is used, not only the water absorption is reduced while maintaining water solubility, but also the irreversible capacity is reduced, and a binder capable of imparting good flexibility to an electrode can be provided.
[0062] The upper and lower limits of the content of the hydroxyalkyl (meth)acrylate having a hydroxyalkyl group having 2 to 4 carbon atoms relative to 100 mol% of the monomer group are exemplified by 60 mol%, 56 mol%, 55 mol%, 50 mol%, 45 mol%, 40 mol%, 35 mol%, 30 mol%, 28.5 mol%, 25 mol%, 20 mol%, 15 mol%, 10 mol%, 5 mol%, 0 mol%, etc. In one embodiment, the above content is preferably 0 mol% to 60 mol%, more preferably 15 mol% to 60 mol%.
[0063] The upper and lower limits of the content of the hydroxyalkyl (meth)acrylate having a hydroxyalkyl group having 2 to 4 carbon atoms relative to 100 mass % of the monomer group are exemplified by 80 mass %, 75 mass %, 70 mass %, 65 mass %, 60 mass %, 55 mass %, 50 mass %, 45 mass %, 40 mass %, 36.7 mass %, 35 mass %, 30 mass %, 25 mass %, 20 mass %, 15 mass %, 10 mass %, 5 mass %, 0 mass %, etc. In one embodiment, the above content is preferably 0 mass % to 80 mass %.
[0064] ((Meth)acrylamide group-containing compound)
[0065] In one embodiment, the monomer group may include a (meth)acrylamide-containing compound. In the present disclosure, "a (meth)acrylamide-containing compound" refers to a compound having a (meth)acrylamide group. The (meth)acrylamide-containing compound may be used alone or in combination of two or more.
[0066] In one embodiment, the (meth)acrylamide-containing compound is represented by the following structural formula:
[0067] [Chemistry 1]
[0068]
[0069] (Where R 1 is a hydrogen atom or a methyl group; R 2 and R 3 are each independently a hydrogen atom, a substituted or unsubstituted alkyl group, or an acetyl group, or R 2 and R 3 are groups that together form a ring structure; R 4 and R 5 are each independently a hydrogen atom, a substituted or unsubstituted alkyl group, a hydroxyl group, an amino group (-NR a R b (R a and R b Each independently represents a hydrogen atom or a substituted or unsubstituted alkyl group) or an acetyl group. Examples of substituents of the substituted alkyl group include hydroxyl, amino, acetyl, and the like. 2 and R 3 Examples of the groups that form a ring structure together include morpholino and the like. )
[0070] Examples of the alkyl group include a linear alkyl group, a branched alkyl group, and a cycloalkyl group.
[0071] Straight chain alkyl is composed of the general formula -C n H 2n+1 (n is an integer greater than or equal to 1). Examples of the linear alkyl group include methyl, ethyl, propyl, n-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, and n-decyl.
[0072] The branched alkyl group is a group in which at least one hydrogen atom of a linear alkyl group is substituted by an alkyl group. Examples of the branched alkyl group include isopropyl, isobutyl, sec-butyl, tert-butyl, diethylpentyl, trimethylbutyl, trimethylpentyl, and trimethylhexyl.
[0073] Examples of the cycloalkyl group include a monocyclic cycloalkyl group, a bridged ring cycloalkyl group, and a condensed ring cycloalkyl group.
[0074] In the present disclosure, a monocyclic ring refers to a ring structure formed by a covalent bond of carbon and having no internal bridge structure. In addition, a fused ring refers to a ring structure in which two or more monocyclic rings share two atoms (i.e., each ring only shares (condenses) one side with each other). A bridged ring refers to a ring structure in which two or more monocyclic rings share three or more atoms.
[0075] Examples of the monocyclic cycloalkyl group include cyclopentyl, cyclohexyl, cycloheptyl, cyclodecyl, and 3,5,5-trimethylcyclohexyl.
[0076] Examples of the bridged cycloalkyl group include tricyclodecanyl, adamantyl, and norbornyl.
[0077] Examples of the fused ring cycloalkyl group include bicyclodecanyl and the like.
[0078] Examples of the (meth)acrylamide group-containing compound include (meth)acrylamide, N-isopropyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dimethylaminopropyl (meth)acrylamide, N-hydroxymethyl (meth)acrylamide, diacetone (meth)acrylamide, maleic acid amide (maleic acid amide), (meth)acryloyl morpholine, hydroxyethyl (meth)acrylamide, and salts thereof. Examples of the salt include dimethylaminopropyl (meth)acrylamide methyl chloride quaternary salt (Methyl quaternary salt), dimethylaminoethyl (meth)acrylate benzyl chloride quaternary salt (benzyl quaternary salt), and the like. Among them, when (meth)acrylamide, especially acrylamide, is used, not only the water absorption is reduced while maintaining water solubility, but also the irreversible capacity is reduced, and a binder with high interaction with electrode active materials, high dispersibility in slurry, and high adhesion between electrode active materials in the electrode can be produced.
[0079] The upper and lower limits of the content of the (meth)acrylamide group-containing compound relative to 100 mol% of the monomer group are exemplified by 90 mol%, 89.95 mol%, 85 mol%, 80 mol%, 75 mol%, 70 mol%, 69.8 mol%, 65 mol%, 60 mol%, 59.95 mol%, 55 mol%, 50 mol%, 45 mol%, 40 mol%, 35 mol%, 34.6 mol%, 30 mol%, 25 mol%, 20 mol%, 15 mol%, 10 mol%, 5 mol%, 4 mol%, 3.8 mol%, 3 mol%, 2 mol%, 1 mol%, 0 mol%, etc. In one embodiment, the above content is preferably 0 mol% to 90 mol%.
[0080] The upper and lower limits of the content of the (meth)acrylamide group-containing compound relative to 100 mass% of the monomer group are exemplified by 90 mass%, 85 mass%, 80 mass%, 75 mass%, 70 mass%, 65 mass%, 60 mass%, 55 mass%, 50 mass%, 45 mass%, 40 mass%, 35 mass%, 30 mass%, 25 mass%, 20 mass%, 15 mass%, 10 mass%, 5 mass%, 0 mass%, etc. In one embodiment, the above content is preferably 0 mass% to 90 mass%.
[0081] (Unsaturated sulfonic acid)
[0082] In one embodiment, the monomer group may include an unsaturated sulfonic acid. The unsaturated sulfonic acid may be used alone or in combination of two or more.
[0083] Examples of the unsaturated sulfonic acid include α,β-ethylenically unsaturated sulfonic acids such as vinylsulfonic acid, styrylsulfonic acid, and (meth)allylsulfonic acid; (meth)acrylamide-tert-butylsulfonic acid, 2-(meth)acrylamide-2-methylpropanesulfonic acid, 2-(meth)acrylamide-2-hydroxypropanesulfonic acid, 3-sulfopropane (meth)acrylate, and bis-(3-sulfopropyl)itaconate.
[0084] The upper and lower limits of the content of the unsaturated sulfonic acid relative to 100 mol% of the monomer group are exemplified by 20 mol%, 17 mol%, 15 mol%, 13 mol%, 10 mol%, 9 mol%, 7 mol%, 5 mol%, 4 mol%, 2 mol%, 1 mol%, 0.9 mol%, 0.7 mol%, 0.5 mol%, 0.3 mol%, 0.2 mol%, 0.1 mol%, 0.09 mol%, 0.07 mol%, 0.05 mol%, 0.03 mol%, 0.01 mol%, 0 mol%, etc. In one embodiment, the content is preferably 0 mol% to 20 mol%.
[0085] The upper and lower limits of the content of the unsaturated sulfonic acid relative to 100 mass % of the monomer group are exemplified by 30 mass %, 25 mass %, 20 mass %, 17 mass %, 15 mass %, 13 mass %, 10 mass %, 9 mass %, 7 mass %, 5 mass %, 4 mass %, 2 mass %, 1 mass %, 0.9 mass %, 0.7 mass %, 0.5 mass %, 0.3 mass %, 0.2 mass %, 0.1 mass %, 0.09 mass %, 0.07 mass %, 0.05 mass %, 0.03 mass %, 0.01 mass %, 0 mass %, etc. In one embodiment, the above content is preferably 0 mass % to 30 mass %.
[0086] (Unsaturated phosphoric acid)
[0087] In one embodiment, the monomer group may include unsaturated phosphoric acid. The unsaturated phosphoric acid may be used alone or in combination of two or more.
[0088] Examples of the unsaturated phosphoric acid include vinylphosphonic acid, vinyl phosphate, bis((meth)acryloyloxyethyl)phosphate, diphenyl-2-(meth)acryloyloxyethyl phosphate, dibutyl-2-(meth)acryloyloxyethyl phosphate, dioctyl-2-(meth)acryloyloxyethyl phosphate, monomethyl-2-(meth)acryloyloxyethyl phosphate, and 3-(meth)acryloyloxy-2-hydroxypropanephosphoric acid.
[0089] The upper and lower limits of the content of the unsaturated phosphoric acid relative to 100 mol% of the monomer group are exemplified by 10 mol%, 9 mol%, 7 mol%, 5 mol%, 4 mol%, 2 mol%, 1 mol%, 0.9 mol%, 0.7 mol%, 0.5 mol%, 0.3 mol%, 0.2 mol%, 0.1 mol%, 0.09 mol%, 0.07 mol%, 0.05 mol%, 0.03 mol%, 0.01 mol%, 0 mol%, etc. In one embodiment, the above content is preferably 0 mol% to 10 mol.
[0090] The upper and lower limits of the content of the unsaturated phosphoric acid relative to 100 mass % of the monomer group are exemplified by 20 mass %, 17 mass %, 15 mass %, 13 mass %, 10 mass %, 9 mass %, 7 mass %, 5 mass %, 4 mass %, 2 mass %, 1 mass %, 0.9 mass %, 0.7 mass %, 0.5 mass %, 0.3 mass %, 0.2 mass %, 0.1 mass %, 0.09 mass %, 0.07 mass %, 0.05 mass %, 0.03 mass %, 0.01 mass %, 0 mass %, etc. In one embodiment, the above content is preferably 0 mass % to 20 mass %.
[0091] (α,β-Unsaturated Nitrile)
[0092] In one embodiment, the monomer group may include α,β-unsaturated nitrile. α,β-unsaturated nitrile may be used alone or in combination of two or more. α,β-unsaturated nitrile may be suitably used for the purpose of imparting flexibility to the electrode.
[0093] Examples of the α,β-unsaturated nitrile include (meth)acrylonitrile, α-chloro(meth)acrylonitrile, α-ethyl(meth)acrylonitrile, vinylidene cyanide, etc. Among them, (meth)acrylonitrile is preferred, and acrylonitrile is particularly preferred.
[0094] The upper and lower limits of the content of the α,β-unsaturated nitrile relative to 100 mol% of the monomer group are exemplified by 40 mol%, 35 mol%, 30 mol%, 25 mol%, 20 mol%, 15 mol%, 10 mol%, 5 mol%, 0 mol%, etc. In one embodiment, the content is preferably 0 mol% to 40 mol%.
[0095] The upper and lower limits of the content of the α,β-unsaturated nitrile relative to 100 mass % of the monomer group are exemplified by 30 mass %, 25 mass %, 20 mass %, 15 mass %, 10 mass %, 5 mass %, 0 mass %, etc. In one embodiment, the content is preferably 0 mass % to 30 mass %.
[0096] <Monomers other than any of the above: also referred to as other components>
[0097] In the above monomer group, as long as the desired effect of the present invention is not impaired, any monomer (other component) other than unsaturated carboxylic acid or its inorganic salt, (meth) hydroxyalkyl acrylate having a hydroxyalkyl group of 2 to 4 carbon atoms, (meth) acrylamide group-containing compound, unsaturated sulfonic acid, unsaturated phosphoric acid, and α,β-unsaturated nitrile can be used. As other components, various well-known components can be used alone, or two or more thereof can be used in combination.
[0098] Examples of other components include unsaturated carboxylic acid esters not containing a hydroxyl group, conjugated dienes, and aromatic vinyl compounds.
[0099] The hydroxyl-free unsaturated carboxylic acid ester is preferably a hydroxyl-free (meth)acrylate. Examples of the hydroxyl-free (meth)acrylate include a hydroxyl-free linear (meth)acrylate, a hydroxyl-free branched (meth)acrylate, a hydroxyl-free alicyclic (meth)acrylate, and a hydroxyl-free alkoxyalkyl (meth)acrylate.
[0100] Examples of the hydroxyl-free linear (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, hexyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, and decyl (meth)acrylate.
[0101] Examples of the branched (meth)acrylate not containing a hydroxyl group include isopropyl (meth)acrylate, isobutyl (meth)acrylate, isoamyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate.
[0102] Examples of the alicyclic (meth)acrylate not containing a hydroxyl group include cyclohexyl (meth)acrylate and the like.
[0103] Examples of the alkoxyalkyl (meth)acrylate not containing a hydroxyl group include methoxymethyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 1-methoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 2-methoxypropyl (meth)acrylate, 1-methoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, 2-methoxybutyl (meth)acrylate, 1-methoxybutyl (meth)acrylate, ethoxymethyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 1-ethoxyethyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 2-ethoxypropyl (meth)acrylate, 1-ethoxypropyl (meth)acrylate, propoxymethyl (meth)acrylate, 2-propoxyethyl (meth)acrylate, 1-propoxyethyl (meth)acrylate, butoxymethyl (meth)acrylate, and the like.
[0104] The unsaturated carboxylic acid ester containing no hydroxyl group can be suitably used for the purpose of imparting flexibility to the electrode. From the above viewpoint, the content of the unsaturated carboxylic acid ester containing no hydroxyl group is preferably less than 30 mol% (e.g., less than 25 mol%, less than 20 mol%, less than 19 mol%, less than 15 mol%, less than 10 mol%, less than 5 mol%, less than 1 mol%, 0 mol%) relative to 100 mol% of the above monomer group.
[0105] In addition, relative to 100 mass % of the above-mentioned monomer group, the content of the unsaturated carboxylic acid ester not containing a hydroxyl group is preferably 30 mass % or less (for example, less than 25 mass %, less than 20 mass %, less than 19 mass %, less than 15 mass %, less than 10 mass %, less than 5 mass %, less than 1 mass %, 0 mass %).
[0106] Examples of the conjugated diene include 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, substituted straight-chain conjugated pentadiene, and substituted side-chain conjugated hexadiene (substituted and side-chain conjugated hexadiene).
[0107] From the viewpoint of the cycle characteristics of the lithium ion battery, the content of the conjugated diene is preferably less than 10 mol %, more preferably 0 mol %, based on 100 mol % of the monomer group.
[0108] The upper and lower limits of the content of the conjugated diene relative to 100 mass % of the monomer group are exemplified by 30 mass %, 20 mass %, 10 mass %, 5 mass %, 1 mass %, 0 mass %, etc. In one embodiment, the content is preferably 0 mass % to 30 mass %.
[0109] Examples of the aromatic vinyl compound include styrene, α-methylstyrene, p-methylstyrene, vinyltoluene, chlorostyrene, and divinylbenzene.
[0110] From the viewpoint of the cycle characteristics of the lithium ion battery, the content of the aromatic vinyl compound is preferably less than 10 mol %, more preferably 0 mol %, based on 100 mol % of the monomer group.
[0111] The upper and lower limits of the content of the aromatic vinyl compound relative to 100 mass % of the monomer group are exemplified by 30 mass %, 20 mass %, 10 mass %, 5 mass %, 1 mass %, 0 mass %, etc. In one embodiment, the content is preferably 0 mass % to 30 mass %.
[0112] The proportion of other components other than the unsaturated carboxylic acid ester not containing a hydroxyl group, the conjugated diene, and the aromatic vinyl compound in the monomer group may be, for example, less than 10 mol%, less than 5 mol%, less than 2 mol%, less than 1 mol%, less than 0.9 mol%, less than 0.5 mol%, less than 0.4 mol%, less than 0.3 mol%, less than 0.1 mol%, less than 0.05 mol%, less than 0.01 mol%, or 0 mol%, relative to 100 mol% of the monomer group. In addition, the proportion may be, for example, less than 10 mol%, less than 9 mol%, less than 7 mol%, less than 5 mol%, less than 4 mol%, less than 2 mol%, less than 1 mol%, less than 0.9 mol%, less than 0.5 mol%, less than 0.4 mol%, less than 0.3 mol%, less than 0.1 mol%, less than 0.05 mol%, less than 0.01 mol%, or 0 mol%, relative to 100 mass% of the monomer group.
[0113] <Method for producing component (A)>
[0114] The component (A) can be synthesized using various known polymerization methods, preferably using a free radical polymerization method. Specifically, it is preferred to add a free radical polymerization initiator and, if necessary, a chain transfer agent to a monomer mixture containing the above components, and perform a polymerization reaction at a reaction temperature of 50° C. to 100° C. while stirring. The reaction time is not particularly limited, but is preferably 1 to 10 hours.
[0115] The free radical polymerization initiator is not particularly limited, and various known free radical polymerization initiators can be used. Examples of free radical polymerization initiators include persulfates such as potassium persulfate and ammonium persulfate; redox polymerization initiators in which the above persulfates are combined with reducing agents such as sodium bisulfite; azo initiators such as 2,2′-azobis-2-amidinopropane dihydrochloride, etc. The amount of the free radical polymerization initiator used is not particularly limited, and is preferably 0.05% to 5.0% by mass, and more preferably 0.1% to 3.0% by mass, relative to 100% by mass of the monomer group providing component (A).
[0116] Before the free radical polymerization reaction and / or when the obtained component (A) is dissolved in water, the pH of the reaction solution may be adjusted using a common neutralizing agent such as ammonia and organic amines, potassium hydroxide, sodium hydroxide, lithium hydroxide, etc., for the purpose of improving the manufacturing stability. In this case, the pH is preferably 2 to 11. In addition, ethylenediaminetetraacetic acid (EDTA) or its salts may be used as metal ion sealants for the same purpose.
[0117] <(A) Physical properties of components>
[0118] From the viewpoint of suppressing the occurrence of cracks and curling of the electrode, the glass transition temperature of the component (A) is 110° C. or lower.
[0119] The upper limit and lower limit of the glass transition temperature of the component (A) are exemplified by 110°C, 105°C, 100°C, 95°C, 90°C, 85°C, 80°C, 75°C, 70°C, 65°C, 60°C, 55°C, 50°C, 45°C, 40°C, 35°C, 30°C, 25°C, 20°C, 15°C, 10°C, etc. In one embodiment, the glass transition temperature of the component (A) is preferably 10°C to 110°C in consideration of the discharge capacity retention rate.
[0120] The glass transition temperature of the component (A) can be calculated as follows: The glass transition temperature can be adjusted by the combination of monomers.
[0121] (1) When the structural monomer of component (A) is known
[0122] The glass transition temperature of the component (A) can be determined from the glass transition temperature (Tg) (absolute temperature: K) of the homopolymer of the monomer and their mass fractions according to the Fox equation shown below.
[0123] 1 / Tg=(W1 / Tg1)+(W2 / Tg2)+(W3 / Tg3)+…+(W n / Tg n )
[0124] [Wherein, Tg represents the glass transition temperature (K) of the polymer to be determined, W1~W n Indicates the mass fraction of each monomer, Tg1~Tg n represents the glass transition temperature (K) of each monomer homopolymer].
[0125] For example, the glass transition temperature is 165°C for acrylamide homopolymers, 106°C for acrylic acid homopolymers, -15°C for hydroxyethyl acrylate homopolymers, and 105°C for acrylonitrile homopolymers. In order to obtain the (A) component having the desired glass transition temperature, the composition of the monomers constituting it can be determined. In addition, the glass transition temperature of the homopolymer of the monomer can be measured by DSC (differential scanning calorimeter), DTA (differential thermal analyzer), TMA (thermomechanical measuring device), etc., for example, under conditions of heating from -100°C to 300°C (heating rate 10°C / min.). In addition, the values recorded in the literature can also be used. The literature exemplifies "Chemical Handbook (Chemical Handbook) Basics II Edited by the Chemical Society of Japan (Revised 5th Edition)", p325, etc.
[0126] (2) When the structural monomer of component (A) is unknown
[0127] The glass transition temperature of the component (A) was measured by DSC (differential scanning calorimeter) under the condition of heating from -100°C to 300°C (temperature increase rate: 10°C / min.).
[0128] The weight average molecular weight (Mw) of the component (A) is not particularly limited, and the upper and lower limits thereof are exemplified by 6 million, 5.5 million, 5 million, 4.5 million, 4 million, 3.5 million, 3 million, 2.5 million, 2 million, 1.5 million, 1 million, 950,000, 900,000, 850,000, 800,000, 750,000, 700,000, 650,000, 600,000, 550,000, 500,000, 450,000, 400,000, 350,000, 300,000, etc. In one embodiment, from the viewpoint of the dispersion stability of the slurry, it is preferably 300,000 to 6 million, and more preferably 350,000 to 6 million.
[0129] The number average molecular weight (Mn) of the component (A) is not particularly limited, and the upper and lower limits thereof are exemplified by 6,000,000, 5,500,000, 5,000,000, 4,500,000, 4,000,000, 3,500,000, 3,000,000, 2,500,000, 2,000,000, 1,500,000, 950,000, 900,000, 850,000, 800,000, 750,000, 700,000, 650,000, 600,000, 550,000, 500,000, 450,000, 400,000, 350,000, 300,000, 200,000, 100,000, 50,000, 10,000, etc. In one embodiment, the number average molecular weight (Mn) of the component (A) is preferably 10,000 or more.
[0130] The weight average molecular weight and the number average molecular weight can be determined as polyacrylic acid-equivalent values measured by gel permeation chromatography (GPC) in an appropriate solvent, for example.
[0131] The upper and lower limits of the molecular weight distribution (Mw / Mn) of the component (A) are exemplified by 15, 14, 13, 11, 10, 9, 7.5, 5, 4, 3, 2.9, 2.5, 2, 1.5, 1.1, etc. In one embodiment, the molecular weight distribution (Mw / Mn) of the component (A) is preferably 1.1-15.
[0132] The B-type viscosity of the aqueous solution containing 13% by mass of the component (A) is not particularly limited, and the upper and lower limits thereof are exemplified by 100,000 mPa·s, 90,000 mPa·s, 80,000 mPa·s, 70,000 mPa·s, 60,000 mPa·s, 50,000 mPa·s, 45,000 mPa·s, 40,000 mPa·s, 30,000 mPa·s, 20,000 mPa·s, 10,000 mPa·s, 9000 mPa·s, 8000 mPa·s, 7000 mPa·s, 6000 mPa·s, 5000 mPa·s, 4000 mPa·s, 3000 mPa·s, 2000 mPa·s, 1000 mPa·s, 900 mPa·s, 700 mPa·s, 500 mPa·s, 300 mPa·s, 200 mPa·s, and 100 mPa·s. In one embodiment, the B-type viscosity is preferably in the range of 100 mPa·s to 100,000 mPa·s.
[0133] The B-type viscosity is measured using a B-type viscometer such as "B-type Viscometer BM" manufactured by Toki Sangyo Co., Ltd.
[0134] In one embodiment, the neutralization rate of the carboxyl groups in the component (A) is preferably 50% or more (e.g., 55% or more, 60% or more, 65% or more, 70% or more, 75% or more, 80% or more, 85% or more, 90% or more, 95% or more, 100%). In the present disclosure, the neutralization rate of the carboxyl groups refers to the conversion of the carboxyl groups (-COOH) into the acid radicals (-CO - The above neutralization ratio can be adjusted by inorganic salts such as alkali metal salts and alkaline earth metal salts.
[0135] The upper and lower limits of the content of the component (A) relative to 100% by mass of the aqueous binder solution for lithium ion batteries are exemplified by 20% by mass, 19% by mass, 15% by mass, 14% by mass, 12% by mass, 10% by mass, 9% by mass, 7% by mass, 6% by mass, 5% by mass, 4% by mass, 3% by mass, 2% by mass, 1% by mass, etc. In one embodiment, the content is preferably 1% to 20% by mass.
[0136] <Amino-containing trialkoxysilane hydrolyzate partial condensate (B): also referred to as component (B)>
[0137] The component (B) may be used alone or in combination of two or more.
[0138] In one embodiment, the amino group-containing trialkoxysilane is a compound represented by the following general formula:
[0139] [Chemistry 2]
[0140]
[0141] (Where R s1 It has an amino group (-NR am1 R am2 : R am1 ~R am2 Each of them is independently a hydrogen atom, an alkyl group, an aryl group, etc.; R s2 ~R s4 are each independently an alkyl group. ).
[0142] With amino group (-NR am1 R am2 : R am1 ~R am2 Examples of the group (each independently a hydrogen atom, an alkyl group, an aryl group, etc.) include an amino-substituted alkyl group, etc. The amino-substituted alkyl group is a group in which one of the hydrogen atoms constituting the alkyl group is substituted with an amino group.
[0143] Examples of the amino group-containing trialkoxysilane include 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2(aminoethyl)3-aminopropyltrimethoxysilane, N-2(aminoethyl)3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylene)propylamine, and N-phenyl-3-aminopropyltrimethoxysilane.
[0144] In the present disclosure, "a hydrolyzed partial condensate of trialkoxysilane" refers to a hydrolyzed partial condensate in which an alkoxy group is present. The residual rate of the hydrolyzable group is not particularly limited. In the present disclosure, from the viewpoint of not gelling, a hydrolyzed partial condensate of trialkoxysilane is used instead of a hydrolyzed complete condensate of trialkoxysilane. A hydrolyzed partial condensate of an amino group-containing trialkoxysilane refers to a hydrolyzed partial condensate of a trialkoxysilane having an amino group.
[0145] The upper and lower limits of the condensation degree of the hydrolyzed partial condensate of the amino group-containing trialkoxysilane are exemplified by 1000, 900, 800, 700, 600, 500, 400, 300, 200, 100, 90, 80, 70, 60, 50, 40, 30, 20, 19, 17, 15, 14, 13, 12, 11, 10, 9, 5, 3, 2, 1.7, 1.5, 1.4, 1.2, 1.1, 1.01, etc. In one embodiment, the condensation degree of the hydrolyzed partial condensate of the amino group-containing trialkoxysilane is preferably 1.01 to 1000, more preferably 1.01 to 100.
[0146] The upper and lower limits of the weight average molecular weight of the hydrolyzed partial condensate of amino-containing trialkoxysilane are exemplified by 190,000, 170,000, 150,000, 130,000, 100,000, 90,000, 70,000, 50,000, 30,000, 20,000, 10,000, 9000, 7500, 5000, 2500, 1000, 900, 750, 500, 250, 200, 175, 160, 150, 125, 110, 100, etc. In one embodiment, the weight average molecular weight is preferably 100 to 190,000.
[0147] The hydrolyzed partial condensate of amino-containing trialkoxysilane is obtained by hydrolyzing 100 parts by mass of amino-containing trialkoxysilane in the presence of 0 to 5 parts by mass of an acid catalyst or a base catalyst (preferably an acid catalyst) and partially condensing it. Specifically, it is preferred to react at a reaction temperature of 30°C to 60°C for 0.5 to 5.0 hours while stirring the reaction solution containing the above components.
[0148] Examples of the acid catalyst include nitric acid, hydrochloric acid, sulfurous acid, phosphoric acid, formic acid, and acetic acid.
[0149] Examples of the alkali catalyst include sodium hydroxide, lithium hydroxide, potassium hydroxide, calcium hydroxide, and amine compounds.
[0150] The upper and lower limits of the content of the component (B) relative to 100% by mass of the aqueous binder solution for lithium ion batteries are exemplified by 10% by mass, 9% by mass, 8% by mass, 7% by mass, 6% by mass, 5% by mass, 4.5% by mass, 4% by mass, 3.5% by mass, 3% by mass, 2.5% by mass, 2% by mass, 1.5% by mass, 1% by mass, 0.9% by mass, 0.5% by mass, 0.1% by mass, 0.09% by mass, 0.05% by mass, 0.03% by mass, 0.01% by mass, etc. In one embodiment, the content is preferably 0.01% by mass to 10% by mass.
[0151] The upper and lower limits of the mass ratio [(A) / (B)] of the component (A) to the component (B) contained in the aqueous binder solution for lithium ion batteries are exemplified by 2000, 1750, 1500, 1250, 1000, 750, 500, 250, 100, 75, 50, 25, 10, 5, 2, 1, etc. In one embodiment, the mass ratio [(A) / (B)] is preferably 1 to 2000.
[0152] The upper and lower limits of the molar ratio (amino group / carboxyl group) of the amino group in the hydrolyzed partial condensate (B) of the amino group-containing trialkoxysilane to the carboxyl group in the water-soluble polymer (A) are exemplified by 500, 475, 450, 425, 400, 375, 350, 325, 300, 275, 250, 225, 200, 175, 150, 125, 100, 75, 50, 25, 20, 15, 10, 9, 7, 5, 2, 1, 0.9, 0.5, 0.2, 0.1, 0.05, etc. In one embodiment, the molar ratio is preferably 0.05 or more, more preferably 0.05 to 500.
[0153] <Water>
[0154] Examples of water include ultrapure water, pure water, distilled water, ion-exchanged water, and tap water.
[0155] The upper and lower limits of the water content relative to 100 mass % of the lithium ion battery binder aqueous solution are 99.9 mass %, 99 mass %, 95 mass %, 90 mass %, 85 mass %, 80 mass %, etc. In one embodiment, the water content is preferably 80 mass % to 99.9 mass %.
[0156] The upper and lower limits of the mass ratio of the component (A) to water contained in the aqueous solution of the binder for lithium ion batteries [component (A) / water] are exemplified by 0.25, 0.24, 0.22, 0.20, 0.18, 0.15, 0.12, 0.10, 0.09, 0.07, 0.05, etc. In one embodiment, the mass ratio is preferably 0.05 to 0.25.
[0157] The upper and lower limits of the mass ratio of the component (B) to water contained in the aqueous solution of the binder for lithium ion batteries [component (B) / water] are exemplified by 0.06, 0.05, 0.02, 0.01, 0.009, 0.007, 0.005, 0.003, 0.001, 0.0009, 0.0007, 0.0005, 0.0003, 0.0001, etc. In one embodiment, the mass ratio is preferably 0.0001 to 0.06.
[0158] <Dispersion (emulsion)>
[0159] In one embodiment, the aqueous binder solution for lithium ion batteries includes a dispersion (emulsion).
[0160] Examples of the dispersion (emulsion) include styrene-butadiene copolymer latex, polystyrene polymer latex, polybutadiene polymer latex, acrylonitrile-butadiene copolymer latex, polyurethane polymer latex, polymethyl methacrylate polymer latex, methyl methacrylate-butadiene copolymer latex, polyacrylate polymer latex, vinyl chloride polymer latex, vinyl acetate polymer emulsion, vinyl acetate-ethylene copolymer emulsion, polyethylene emulsion, carboxyl-modified styrene-butadiene copolymer resin emulsion, acrylic resin emulsion, polyethylene, polypropylene, polyethylene terephthalate, polyamide (PA), polyimide (PI), polyamideimide (PAI), aromatic polyamide, alginic acid and its salts, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), ethylene-tetrafluoroethylene copolymer (ETFE), etc.
[0161] Relative to 100 mass % of (A) component, the upper and lower limits of the content of the dispersion (emulsion) are exemplified by 100 mass %, 95 mass %, 90 mass %, 85 mass %, 80 mass %, 75 mass %, 70 mass %, 65 mass %, 60 mass %, 55 mass %, 50 mass %, 45 mass %, 40 mass %, 35 mass %, 30 mass %, 25 mass %, 20 mass %, 19 mass %, 17 mass %, 15 mass %, 13 mass %, 10 mass %, 9 mass %, 7 mass %, 5 mass %, 4 mass %, 2 mass %, 1 mass %, 0 mass %, etc. In one embodiment, from the viewpoint of electrode flexibility and discharge capacity retention rate, the above content is preferably 0 mass % to 100 mass %.
[0162] <Thickener>
[0163] In one embodiment, the aqueous binder solution for lithium ion batteries contains a thickener.
[0164] Examples of thickeners include cellulose polymers such as carboxymethyl cellulose, methyl cellulose, hydroxypropyl cellulose, and their ammonium salts and alkali metal salts; (modified) poly(meth)acrylic acid and their ammonium salts and alkali metal salts; (modified) polyvinyl alcohol, copolymers of acrylic acid or acrylic acid salts and vinyl alcohol, polyvinyl alcohols such as copolymers of maleic anhydride or maleic acid or fumaric acid and vinyl alcohol; polyethylene glycol, polyethylene oxide, polyvinyl pyrrolidone, modified polyacrylic acid, oxidized starch, starch phosphate, casein, various modified starches, acrylonitrile-butadiene copolymer hydrogenates, etc.
[0165] The upper and lower limits of the content of the tackifier relative to 100 mass % of component (A) are exemplified by 50 mass %, 45 mass %, 40 mass %, 35 mass %, 30 mass %, 25 mass %, 20 mass %, 19 mass %, 17 mass %, 15 mass %, 13 mass %, 10 mass %, 9 mass %, 7 mass %, 5 mass %, 4 mass %, 2 mass %, 1 mass %, 0 mass %, etc. In one embodiment, the above content is preferably 0 mass % to 50 mass %.
[0166] <Additives>
[0167] The aqueous binder solution for lithium ion batteries may contain a component that does not belong to any of the component (A), the component (B), water, the dispersion (emulsion), and the thickener as an additive.
[0168] Examples of the additive include a dispersant, a leveling agent, and an antioxidant.
[0169] Examples of the dispersant include anionic dispersants, cationic dispersants, nonionic dispersants, and polymer dispersants.
[0170] Examples of the leveling agent include surfactants such as alkyl surfactants, silicon surfactants, fluorine surfactants, and metal surfactants. By using a surfactant, craters generated during coating can be prevented, and the smoothness of the slurry layer (coating) can be improved.
[0171] Examples of the antioxidant include phenol compounds, hydroquinone compounds, organic phosphine compounds, sulfur compounds, phenylenediamine compounds, polymer phenol compounds, etc. The polymer phenol compound is a polymer having a phenol structure in the molecule. The weight average molecular weight of the polymer phenol compound is preferably 200 to 1000, more preferably 600 to 700.
[0172] Examples of the content of the additive relative to 100 mass% of component (A) or component (B) include less than 5 mass%, less than 4 mass%, less than 2 mass%, less than 1 mass%, less than 0.9 mass%, less than 0.5 mass%, less than 0.4 mass%, less than 0.2 mass%, less than 0.1 mass%, less than 0.09 mass%, less than 0.05 mass%, less than 0.04 mass%, less than 0.02 mass%, less than 0.01 mass%, 0 mass%, etc.
[0173] In addition, the content of the additive relative to 100 mass % of the above-mentioned aqueous solution is exemplified as less than 5 mass %, less than 4 mass %, less than 2 mass %, less than 1 mass %, less than 0.9 mass %, less than 0.5 mass %, less than 0.4 mass %, less than 0.2 mass %, less than 0.1 mass %, less than 0.09 mass %, less than 0.05 mass %, less than 0.04 mass %, less than 0.02 mass %, less than 0.01 mass %, 0 mass %, etc.
[0174] When the pH is 5 or more, the dispersibility of the conductive carbon auxiliary agent is good, and as a result, an excellent discharge capacity retention rate is exhibited. Therefore, the pH of the aqueous binder solution for lithium ion batteries is set to 5 or more.
[0175] Examples of the upper and lower limits of the pH of the aqueous solution of the binder for lithium ion batteries include 9, 8.9, 8.5, 8, 7.9, 7.7, 7.5, 7.3, 7.1, 7, 6.9, 6.7, 6.5, 6.3, 6, 5.9, 5.6, 5.5, 5.4, 5.2, 5.1, and 5.
[0176] The pH can be measured at 25° C. using a glass electrode pH meter (for example, manufactured by Horiba, Ltd., product name “pH meter D-52”).
[0177] The binder aqueous solution for lithium ion batteries can be used as a binder aqueous solution for lithium ion battery electrodes, a binder aqueous solution for lithium ion battery negative electrodes, a conductive carbon auxiliary agent dispersant for lithium ion batteries, and the like.
[0178] [Anode slurry for lithium-ion batteries: also called slurry]
[0179] The present disclosure provides a negative electrode slurry for a lithium ion battery, the negative electrode slurry for a lithium ion battery comprising:
[0180] A water-soluble polymer (A), wherein the water-soluble polymer (A) is a polymer of a monomer group containing 15 mol% to 99.9 mol% of an unsaturated carboxylic acid or an inorganic salt thereof relative to 100 mol% of the monomer group, and has a glass transition temperature of 110°C or less;
[0181] A hydrolyzed partial condensate of an amino group-containing trialkoxysilane (B);
[0182] A negative electrode active material (C); and
[0183] A conductive carbon additive (D) having a zeta potential of 0 mV or more at pH 5 to 7.
[0184] Examples of the water-soluble polymer (A) and the hydrolyzed partial condensate (B) of the amino group-containing trialkoxysilane include those mentioned above.
[0185] In this disclosure, "slurry" refers to a suspension of liquid and solid particles.
[0186] The upper and lower limits of the content of the component (A) relative to 100% by mass of the slurry are exemplified by 10% by mass, 9% by mass, 8% by mass, 7% by mass, 6% by mass, 5% by mass, 4% by mass, 3% by mass, 2% by mass, 1% by mass, 0.9% by mass, 0.7% by mass, 0.5% by mass, 0.3% by mass, 0.1% by mass, etc. In one embodiment, the content is preferably 0.1% to 10% by mass relative to 100% by mass of the slurry.
[0187] The upper and lower limits of the content of the component (B) relative to 100% by mass of the slurry are exemplified by 5% by mass, 4% by mass, 3% by mass, 2% by mass, 1% by mass, 0.9% by mass, 0.7% by mass, 0.5% by mass, 0.3% by mass, 0.1% by mass, 0.09% by mass, 0.07% by mass, 0.05% by mass, 0.03% by mass, 0.01% by mass, etc. In one embodiment, the content is preferably 0.01% to 5% by mass.
[0188] The upper and lower limits of the water content relative to 100 mass % of the slurry are exemplified by 70 mass %, 65 mass %, 60 mass %, 55 mass %, 50 mass %, 45 mass %, 40 mass %, 35 mass %, 30 mass %, etc. In one embodiment, the water content is preferably 30 mass % to 70 mass %.
[0189] <Negative Electrode Active Material (C): Also Called (C) Component>
[0190] The negative electrode active material may be used alone or in combination of two or more.
[0191] As long as it is a material that can reversibly absorb and release lithium, the negative electrode active material is not particularly limited, and a suitable material can be appropriately selected according to the type of the target lithium ion battery, and can be used alone or in combination of two or more. Examples of the negative electrode active material include carbon materials and silicon materials, oxides containing lithium atoms, lead compounds, tin compounds, arsenic compounds, antimony compounds, and aluminum compounds that are alloyed with lithium.
[0192] Examples of the above-mentioned carbon materials include graphite (also called black lead, examples include natural graphite, artificial graphite, etc.) as highly crystalline carbon, low-crystalline carbon (soft carbon, hard carbon), carbon black (ketjen black, acetylene black, channel black, lamp black, oil furnace black, thermal black, etc.), fullerenes, carbon nanotubes, carbon nanofibers, carbon nanohorns, carbon fibrils, mesophase carbon microbeads (MCMB), pitch-based carbon fibers, etc.
[0193] The silicon material includes SiC, SiO x C y (0<x≤3, 0<y≤5); Si3N4; Si2N2O; with SiO x Silicon oxide composites represented by (0<x≤2) (for example, materials described in Japanese Patent Publication No. 2004-185810 and Japanese Patent Publication No. 2005-259697); silicon materials described in Japanese Patent Publication No. 2004-185810, etc. In addition, silicon materials described in Japanese Patent No. 5390336 and Japanese Patent No. 5903761 can also be used.
[0194] The silicon oxide is preferably of the composition formula SiO x Silicon oxide represented by (0<x<2, preferably 0.1≤x≤1).
[0195] The silicon alloy is preferably an alloy of silicon and at least one transition metal, and the transition metal is selected from the group consisting of titanium, zirconium, nickel, copper, iron and molybdenum. These transition metal silicon alloys have high electronic conductivity and high strength, so they are preferred. Silicon alloys are more preferably silicon-nickel alloys or silicon-titanium alloys, and are particularly preferably silicon-titanium alloys. Relative to 100 mol% of the metal elements in the above alloy, the content of silicon in the silicon alloy is preferably 10 mol% or more, and more preferably 20 mol% to 70 mol%. In addition, the silicon material can be any of single crystal, polycrystalline and amorphous.
[0196] In addition, when a silicon material is used as the negative electrode active material, a negative electrode active material other than a silicon material may be used in combination. Examples of such negative electrode active materials include the above-mentioned carbon material; conductive polymers such as polyphenylene; X B Y O Z (A represents an alkali metal or a transition metal; B represents at least one transition metal selected from cobalt, nickel, aluminum, tin, manganese, etc.; O represents an oxygen atom; X, Y and Z are numbers in the range of 0.05<X<1.10, 0.85<Y<4.00, 1.5<Z<5.00, respectively) represented by a composite metal oxide; and other metal oxides, etc. When a silicon material is used as a negative electrode active material, the volume change accompanying the absorption and release of lithium is small, so it is preferably used in combination with a carbon material.
[0197] Examples of the above-mentioned oxides containing lithium atoms include ternary nickel cobalt manganese oxide, lithium-manganese composite oxides (LiMn2O4, etc.), lithium-nickel composite oxides (LiNiO2, etc.), lithium-cobalt composite oxides (LiCoO2, etc.), lithium-iron composite oxides (LiFeO2, etc.), lithium-nickel-manganese composite oxides (LiNi 0.5Mn 0.5 O2, etc.), lithium-nickel-cobalt composite oxide (LiNi 0.8 Co 0.2 O2, etc.), lithium-transition metal phosphate compounds (LiFePO4, etc.) and lithium-transition metal sulfate compounds (Li x Fe2(SO4)3), lithium-titanium composite oxide (lithium titanate: Li4Ti5O 12 ) and other lithium-transition metal composite oxides and other previously known negative electrode active materials.
[0198] From the viewpoint of significantly exerting the effects of the present invention, the carbon material and / or the material alloying with lithium contained in the negative electrode active material is preferably 50 mass % or more, more preferably 80 mass % or more, further preferably 90 mass % or more, particularly preferably 100 mass %.
[0199] In one embodiment, the negative electrode active material (C) is preferably a negative electrode active material containing more than 1 mass % (more than 2 mass %, more than 5 mass %, more than 10 mass %, more than 25 mass %, more than 50 mass %, more than 75 mass %, more than 90 mass %, 100 mass %) of silicon and / or silicon oxide covered with a carbon layer.
[0200] The shape of the negative electrode active material is not particularly limited, and can be any shape such as microparticles and thin films, preferably microparticles. The average particle size of the negative electrode active material is not particularly limited, and its upper and lower limits are exemplified by 50μm, 45μm, 40μm, 35μm, 30μm, 25μm, 20μm, 15μm, 10μm, 5μm, 4μm, 3μm, 2.9μm, 2μm, 1μm, 0.5μm, 0.1μm, etc. More specifically, in one embodiment, from the viewpoint of uniformly forming a thin coating film, if it is above 0.1μm, the operability is good, and if it is below 50μm, it is easy to coat the electrode, so the average particle size of the negative electrode active material is preferably 0.1μm to 50μm, more preferably 0.1μm to 45μm, further preferably 1μm to 10μm, and particularly preferably 5μm.
[0201] In the above slurry, relative to 100% by mass of the negative electrode active material (C), the upper and lower limits of the content of the (A) component are exemplified as 15% by mass, 14% by mass, 13% by mass, 12% by mass, 11% by mass, 10% by mass, 9% by mass, 8% by mass, 7% by mass, 6% by mass, 5% by mass, 4% by mass, 3% by mass, 2% by mass, 1.5% by mass, 1% by mass, 0.5% by mass, etc. In one embodiment, the above content is preferably 0.5% by mass to 15% by mass.
[0202] Conductive carbon additive (D) with a ζ-potential of 0 mV or more at pH 5 to 7: Also referred to as component (D)
[0203] The conductive carbon additive (D) with a ζ-potential of 0 mV or more at pH 5 to 7 can be used alone or in combination of two or more.
[0204] Examples of the conductive carbon additive with a ζ-potential of 0 mV or more at pH 5 to 7 include fibrous carbon, graphite particles, carbon black, etc.
[0205] Examples of fibrous carbon include vapor-grown carbon fiber (VGCF), carbon nanotube (CNT), carbon nanofiber (CNF), etc.
[0206] Examples of carbon black include acetylene black, Ketjen black, furnace black, etc.
[0207] In one embodiment, the conductive carbon additive with a ζ-potential of 0 mV or more at pH 5 to 7 is preferably carbon black.
[0208] As long as component (D) is a conductive carbon additive with a ζ-potential of 0 mV or more at pH 5 to 7. The shape of component (D) is not particularly limited. The dispersibility of the conductive carbon additive can be judged according to the magnitude of the absolute value of the ζ-potential. The ζ-potential is an index indicating the degree of the surface charge amount of particles. The larger the absolute value of the ζ-potential of particle A, the stronger the repulsive force between particle A, and the easier it is to disperse. On the contrary, the smaller the absolute value of the ζ-potential of particle A, the easier it is for particle A to aggregate. The conductive carbon additive with a ζ-potential of 0 mV or more, especially 0 mV to 30 mV, at pH 5 to 7 has low initial dispersibility and dispersion stability. However, the negative electrode paste for a lithium ion battery containing component (A), component (B), and the conductive carbon additive with a ζ-potential of 0 mV or more at pH 5 to 7 shows high initial dispersibility and dispersion stability.
[0209] The ζ-potential of the conductive carbon additive at pH 5 to 7 can be measured at 25 °C (for example, at pH 6.1) using a ζ-potential and particle size measurement system (manufactured by Otsuka Electronics Co., Ltd., product name “ELSZ-1000Z”). A solution containing the conductive carbon additive can be prepared by using water as a solvent, adding the conductive carbon additive, and stirring. In addition, the pH of this solution can be adjusted by adding hydrochloric acid or sodium hydroxide.
[0210] The upper limit and lower limit of the content of the component (D) relative to 100% by mass of the slurry are exemplified by 6%, 5%, 4%, 3%, 2%, 1.9%, 1.7%, 1.5%, 1.3%, 1.1%, 1%, 0.9%, 0.7%, 0.5%, 0.3%, 0.1%, 0.09%, 0.07%, 0.05%, 0.03%, 0.01%, 0.009%, 0.007%, 0.005%, 0.003%, 0.001%, 0.0009%, 0.0007%, 0.0005%, 0.0003%, 0.0001%, etc. In one embodiment, the content is preferably 0.0001% by mass to 6% by mass.
[0211] <Conductive Aids Other Than Component (D)>
[0212] In one embodiment, the slurry may contain a conductive aid other than component (D). Examples of conductive aids other than component (D) include carbon black having a zeta potential of less than 0 mV at pH 5 to 7, Cu, Ni, Al, Si or alloys thereof having an average particle size of less than 10 μm, etc. The content of conductive aids other than component (D) is not particularly limited, and is preferably 0 to 10 parts by mass, more preferably 0.001 to 6 parts by mass, relative to 100 parts by mass of the negative electrode active material.
[0213] <Slurry Viscosity Adjusting Solvent>
[0214] The slurry viscosity adjusting solvent is not particularly limited, and may include a non-aqueous medium having a normal boiling point of 80° C. to 350° C. The slurry viscosity adjusting solvent may be used alone or in combination of two or more. Examples of the slurry viscosity adjusting solvent include amide solvents such as N-methylpyrrolidone, dimethylformamide, and N,N-dimethylacetamide; hydrocarbon solvents such as toluene, xylene, n-dodecane, and tetralin; alcohol solvents such as methanol, ethanol, 2-propanol, isopropanol, 2-ethyl-1-hexanol, 1-nonanol, and lauryl alcohol; ketone solvents such as acetone, methyl ethyl ketone, cyclohexanone, phorone, acetophenone, and isophorone; ether solvents such as dioxane and tetrahydrofuran (THF); ester solvents such as benzyl acetate, isoamyl butyrate, methyl lactate, ethyl lactate, and butyl lactate; amine solvents such as o-toluidine, m-toluidine, and p-toluidine; lactones such as γ-butyrolactone and δ-butyrolactone; sulfoxide / sulfone solvents such as dimethyl sulfoxide and sulfolane; water, etc. Among them, N-methylpyrrolidone is preferred from the viewpoint of coating workability. The content of the non-aqueous medium is not particularly limited, but is preferably 0% by mass to 10% by mass relative to 100% by mass of the slurry.
[0215] The slurry may contain any component other than component (A), component (B), component (C), component (D), water, a conductive additive other than component (D), or a slurry viscosity adjusting solvent as an additive within the range that does not impair the effects of the present invention. Examples of the additive include the above-mentioned additives.
[0216] The content of the additive relative to 100 mass% of any one of the components (A) to (D) is exemplified by less than 5 mass%, less than 4 mass%, less than 2 mass%, less than 1 mass%, less than 0.9 mass%, less than 0.5 mass%, less than 0.4 mass%, less than 0.2 mass%, less than 0.1 mass%, less than 0.09 mass%, less than 0.05 mass%, less than 0.04 mass%, less than 0.02 mass%, less than 0.01 mass%, 0 mass%, etc.
[0217] In addition, about the dispersion (emulsion), it can also be contained in an amount greater than the content of the above-mentioned additive. Relative to 100% by mass of the negative electrode slurry for lithium ion batteries, the upper and lower limits of the content of the dispersion (emulsion) are exemplified as 20% by mass, 19% by mass, 17% by mass, 15% by mass, 13% by mass, 10% by mass, 9% by mass, 7% by mass, 5% by mass, 4% by mass, 2% by mass, 1% by mass, 0% by mass, etc. In one embodiment, from the viewpoint of electrode flexibility and discharge capacity retention rate, the addition amount of the dispersion (emulsion) is preferably less than 5% by mass relative to 100% by mass of the above-mentioned aqueous solution or the above-mentioned negative electrode slurry for lithium ion batteries.
[0218] Examples of the upper and lower limits of the pH of the slurry include 9, 8.9, 8.5, 8, 7.9, 7.7, 7.5, 7.3, 7.1, 7, 6.9, 6.7, 6.5, 6.3, 6, 5.9, 5.6, 5.5, 5.4, 5.2, 5.1, and 5.
[0219] The slurry is produced by mixing the components (A), (B), (C), and (D) with water and, if necessary, a conductive additive other than the component (D), a slurry viscosity adjusting solvent, and additives.
[0220] Examples of the mixing means for the slurry include a ball mill, a sand mill, a pigment disperser, a pounder, an ultrasonic disperser, a homogenizer, a planetary mixer, and a Hobart mixer.
[0221] [Negative electrode for lithium-ion batteries]
[0222] The present disclosure provides a negative electrode for a lithium ion battery obtained by applying the negative electrode slurry for a lithium ion battery on a current collector and drying and solidifying the negative electrode slurry. The negative electrode for a lithium ion battery has a solidified product of the negative electrode slurry for a lithium ion battery on the surface of the current collector.
[0223] The current collector may be any of various known current collectors without particular limitation. The material of the current collector is not particularly limited, and examples thereof include metal materials such as copper, iron, aluminum, nickel, stainless steel, and nickel-plated steel; and carbon materials such as carbon cloth and carbon paper. The shape of the current collector is also not particularly limited, and in the case of metal materials, examples thereof include metal foil, metal cylinder, metal coil, and metal plate; and in the case of carbon materials, examples thereof include carbon plate, carbon film, and carbon cylinder. Among them, in the case of using the negative electrode active material for the negative electrode, copper foil is preferably used as the current collector because it is currently used in industrial products.
[0224] The coating means is not particularly limited, and examples thereof include conventionally known coating devices such as a comma coater, a gravure coater, a micro gravure coater, a die coater, and a bar coater.
[0225] The drying means is not particularly limited, but the temperature is preferably 60° C. to 200° C., more preferably 60° C. to 180° C. The atmosphere may be dry air or an inert atmosphere.
[0226] The thickness of the negative electrode (cured product) is not particularly limited, but is preferably 5 μm to 300 μm, more preferably 10 μm to 250 μm. Within the above range, a sufficient Li absorption and release function for a high-density current value can be easily obtained.
[0227] [Lithium-ion battery]
[0228] The present disclosure provides a lithium ion battery including the above-mentioned negative electrode for lithium ion battery. The above-mentioned battery also includes an electrolyte solution and a packaging material, which are not particularly limited.
[0229] Examples of the electrolyte solution include a non-aqueous electrolyte solution in which a supporting electrolyte is dissolved in a non-aqueous solvent. The non-aqueous electrolyte solution may contain a film-forming agent.
[0230] The non-aqueous solvent may be any known non-aqueous solvent without particular limitation, and may be used alone or in combination of two or more. Examples of the non-aqueous solvent include chain carbonate solvents such as diethyl carbonate, dimethyl carbonate, and ethyl methyl carbonate; cyclic carbonate solvents such as ethylene carbonate, propylene carbonate, and butylene carbonate; chain ether solvents such as 1,2-dimethoxyethane; cyclic ether solvents such as tetrahydrofuran, 2-methyltetrahydrofuran, sulfolane, and 1,3-dioxolane; chain ester solvents such as methyl formate, methyl acetate, and methyl propionate; cyclic ester solvents such as γ-butyrolactone and γ-valerolactone; acetonitrile, etc. Among them, a combination of mixed solvents containing cyclic carbonates and chain carbonates is preferred.
[0231] A lithium salt may be used as the supporting electrolyte. Various known lithium salts may be used as the lithium salt without particular limitation, and may be used alone or in combination of two or more. Examples of the supporting electrolyte include LiPF6, LiAsF6, LiBF4, LiSbF6, LiAlCl4, LiClO4, CF3SO3Li, C4F9SO3Li, CF3COOLi, (CF3CO)2NLi, (CF3SO2)2NLi, (C2F5SO2)NLi, etc. Among them, LiPF6, LiClO4, and CF3SO3Li, which are easily soluble in a solvent and show a high degree of dissociation, are preferred. The higher the degree of dissociation of the supporting electrolyte used, the higher the lithium ion conductivity, and therefore, the lithium ion conductivity can be adjusted by the type of supporting electrolyte.
[0232] The film forming agent can use various known film forming agents without particular limitation, and can be used alone or in combination of two or more. The film forming agent exemplifies carbonate compounds such as vinylene carbonate, vinyl ethylene carbonate, vinyl ethyl carbonate, methyl phenyl carbonate, fluoroethylene carbonate, and difluoroethylene carbonate; cyclosulfide hydrocarbons such as ethylene sulfide and propylene sulfide; sultone compounds such as 1,3-propane sultone and 1,4-butane sultone; anhydrides such as maleic anhydride and succinic anhydride. The content of the film forming agent in the electrolyte solution is not particularly limited, and is preferably in the order of less than 10% by mass, less than 8% by mass, less than 5% by mass, and less than 2% by mass. By making the content less than 10% by mass, the advantage of the film forming agent is that it is easy to achieve the suppression of the initial irreversible capacity, the improvement of low temperature characteristics and rate characteristics, etc.
[0233] The form of the lithium-ion battery is not particularly limited. Examples of the form of the lithium-ion battery include a cylindrical type in which the electrode sheet and the separator are spirally shaped; a cylindrical type in which the plate electrode and the separator are combined with an inside-out structure; and a button type in which the plate electrode and the separator are stacked. In addition, by placing these batteries in any outer packaging box, they can be used in any shape such as a button type, a cylindrical type, or a square type.
[0234] The manufacturing method of the lithium ion battery is not particularly limited, and can be assembled by taking appropriate procedures according to the structure of the battery. The manufacturing method of the lithium ion battery is exemplified by the method described in Japanese Patent Publication No. 2013-089437. The battery can be manufactured by installing a negative electrode on an outer packaging box, setting an electrolyte and a diaphragm thereon, and then installing a positive electrode so that the positive electrode and the negative electrode are opposite to each other, and fixing them with a gasket and a sealing plate.
[0235] Example
[0236] The present invention is described in detail below by way of examples and comparative examples. However, the description in the above preferred embodiments and the following examples are provided only for the purpose of illustration and are not provided for the purpose of limiting the present invention. Therefore, the scope of the present invention is not limited to the embodiments or examples specifically described in this specification, but is limited only by the scope of the claims. In addition, in each example and comparative example, unless otherwise specified, the numerical values of parts, % and the like are based on mass.
[0237] Example 1-1
[0238] <Production of Water-Soluble Polymer (A)>
[0239] In a reaction apparatus equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube, 1228 g of ion exchange water, 189.8 g (2.10 mol) of 80% acrylic acid, and 0.33 g (0.0021 mol) of sodium methallylsulfonate were added, and after removing oxygen in the reaction system with nitrogen, the temperature was raised to 50° C. 1.4 g of 2,2′-azobis-2-amidinopropane dihydrochloride (2,2′-azobis-2-amidinopropane dihydrochloride) (manufactured by Nihon Chemical Co., Ltd., product name “NC-32”) and 15 g of ion exchange water were added, and the temperature was raised to 80° C. to carry out a reaction for 3 hours. Thereafter, 140.3 g (1.68 mol) of a 48% sodium hydroxide aqueous solution was added as a neutralizing agent and stirred to obtain an aqueous solution containing a water-soluble polymer (A) having a neutralization rate of 80%.
[0240] <Production of Hydrolyzed Partial Condensate of Amino Group-Containing Trialkoxysilane (B)>
[0241] Into a reaction apparatus equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube, 100 g of ion exchange water, 100 g of methanol, 1.23 g of nitric acid, and 200 g of 3-aminopropyltrimethoxysilane (manufactured by Shin-Etsu Chemical Co., Ltd., product name "KBM-903") were added, and the mixture was reacted at 25°C for 0.5 hour to obtain a uniform aqueous solution of a hydrolyzed partial condensate (B) of an amino-containing trialkoxysilane having a condensation degree of 1.4 and a weight average molecular weight of 160.
[0242] <Manufacturing of Binder Aqueous Solution for Lithium Ion Batteries>
[0243] In a reaction apparatus equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet pipe, 10 parts by weight of a hydrolyzed partial condensate (B) of an amino group-containing trialkoxysilane was added to 90 parts by weight of a water-soluble polymer (A) and stirred for 30 minutes to obtain an aqueous binder solution for lithium ion batteries. The aqueous solution had a B-type viscosity of 12,810 mPa·s at 25° C. and a pH of 7.1.
[0244] For Example 1 other than Example 1-1, except that the monomer composition, the amount of the neutralizing agent, and the amount of the hydrolyzed partial condensate (B) of the amino-containing trialkoxysilane in the above Example 1-1 were changed as shown in Table 1, an aqueous binder solution for lithium ion batteries containing a water-soluble polymer (A) and a hydrolyzed partial condensate (B) of the amino-containing trialkoxysilane was obtained in the same manner as Example 1-1.
[0245] Comparative Example 1-1
[0246] In a reaction apparatus equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen inlet tube, 1228 g of ion exchange water, 189.8 g (2.10 mol) of 80% acrylic acid, and 0.33 g (0.0021 mol) of sodium methallyl sulfonate were added, and the oxygen in the reaction system was removed by nitrogen, and the temperature was raised to 50°C. 1.4 g of 2,2′-azobis-2-amidinopropane dihydrochloride (manufactured by Nihon Kagaku Co., Ltd., product name "NC-32") and 15 g of ion exchange water were added thereto, and the temperature was raised to 80°C for 3 hours to react. Thereafter, 140.3 g (1.68 mol) of a 48% sodium hydroxide aqueous solution was added as a neutralizing agent and stirred to obtain an aqueous solution containing a water-soluble polymer. The B-type viscosity of the aqueous solution at 25°C was 12,520 mPa·s, and the pH was 6.1.
[0247] Regarding Comparative Example 1 other than Comparative Example 1-1, a lithium ion battery binder aqueous solution was obtained in the same manner as in Example 1-1 except that the monomer composition, the amount of the neutralizer, and the amount of the hydrolyzed partial condensate (B) of the amino group-containing trialkoxysilane were changed as shown in Table 1.
[0248] [Table 1]
[0249]
[0250] ※The neutralization ratio is a value relative to the carboxyl groups contained in the component (A).
[0251] AA: Acrylic acid (manufactured by Osaka Organic Chemical Industry Co., Ltd., "80% acrylic acid")
[0252] HEA: 2-Hydroxyethyl acrylate (manufactured by Osaka Organic Chemical Industry Co., Ltd., “HEA”)
[0253] SMAS: Sodium methallyl sulfonate
[0254] AM: Acrylamide (manufactured by Mitsubishi Chemical Co., Ltd., “50% Acrylamide”)
[0255] ·NaOH: Sodium hydroxide (manufactured by Kanto Chemical Co., Ltd., “48% sodium hydroxide solution”)
[0256] Glass transition temperature
[0257] It is a value calculated based on the Fox equation.
[0258] Weight-average molecular weight
[0259] The weight-average molecular weight is determined as a conversion value of polyacrylic acid measured by gel permeation chromatography (GPC) in a 0.2 M phosphate buffer / acetonitrile solution (90 / 10, pH 8.0). The GPC apparatus used is HLC-8220 (manufactured by Tosoh Corporation), and the column used is SB-806M-HQ (manufactured by Shodex).
[0260] pH
[0261] The pH of each aqueous binder solution is measured at 25 °C using a glass electrode pH meter (product name "Handy pH meter D-52", manufactured by Horiba, Ltd.).
[0262] B-type viscosity
[0263] The viscosity of each aqueous binder solution is measured at 25 °C under the following conditions using a B-type viscometer (manufactured by Toki Sangyo Co., Ltd., product name "B-type viscometer TVB-10M").
[0264] When the viscosity is 1,000 mPa·s to less than 10,000 mPa·s: Use a No. 3 rotor and a rotation speed of 12 rpm.
[0265] When the viscosity is 10,000 mPa·s or more: Use a No. 3 rotor and a rotation speed of 6 rpm.
[0266] Manufacture of conductive carbon additive paste
[0267] Example 2-1
[0268] Using a commercially available planetary mixer (product name "Awatori Ren-taro", manufactured by Shinki Co., Ltd.), in a container dedicated to this mixer, 40 parts by mass of the aqueous binder solution for lithium-ion batteries containing the water-soluble polymer (A) and the hydrolyzed partial condensate (B) of the amino group-containing trialkoxysilane obtained in Example 1-1 and 60 parts by mass of carbon black (manufactured by Imerys GC Japan Co., Ltd., "Super C65") with a ζ potential of 16 mV at pH 6.1 are charged. Ion-exchanged water is added thereto so that the solid content concentration is 13.5%, and the container is set in the above planetary mixer. Then, it is kneaded at 2,000 rpm for 10 minutes to obtain a conductive carbon additive paste.
[0269] The zeta potential was measured at 25° C. and pH 6.1 using a zeta potential particle size measurement system (manufactured by Otsuka Electronics Co., Ltd., product name “ELSZ-1000Z”).
[0270] For Example 2 and Comparative Example 2 other than Example 2-1, conductive carbon auxiliary agent pastes were prepared in the same manner as in Example 2-1, except that the composition in Example 2-1 was changed as shown in the following table.
[0271] <Initial Dispersion Test of Conductive Carbon Additive Paste>
[0272] The median particle size "D50" and "D90" of the conductive carbon additive paste obtained in Example 2-1 were measured using a commercially available laser diffraction / scattering particle size distribution measuring device (product name "LA-960", manufactured by HORIBA). The higher the measured "D50" and "D90" values, the worse the initial dispersibility of the conductive additive and the more agglomerated it is. The lower the "D50" and "D90" values, the better the initial dispersibility of the conductive additive.
[0273] The numerical value of the median particle size "D50" was evaluated according to the following evaluation criteria.
[0274] A: 3.5μm or less
[0275] B: more than 3.5μm
[0276] The numerical value of "D90" was evaluated according to the following evaluation criteria.
[0277] A: 7.0μm or less
[0278] B: more than 7.0μm
[0279] <Dispersion stability test of conductive carbon additive paste>
[0280] After the conductive carbon additive paste obtained in Example 2-1 was allowed to stand at room temperature for 24 hours, the median particle sizes "D50" and "D90" were measured. The greater the change in the measured "D50" and "D90" values, the worse the dispersion stability of the conductive carbon additive and the more agglomerated it is. The smaller the change in the "D50" and "D90" values, the better the dispersion stability of the conductive carbon additive. The change rate of "D50" and "D90" is calculated using the following formula, and evaluated according to the following evaluation criteria.
[0281] Change rate of "D50" (%) = {[(D50 of conductive carbon additive paste after 24 hours) - (D50 of conductive carbon additive paste after initial dispersion test)] / (D50 of conductive carbon additive paste after initial dispersion test)} × 100
[0282] Change rate of "D90" (%) = {[(D90 of conductive carbon additive paste after 24 hours) - (D90 of conductive carbon additive paste after initial dispersion test)] / (D90 of conductive carbon additive paste after initial dispersion test)} × 100
[0283] A: less than ±40%
[0284] B: ±40% or more
[0285] [Table 2]
[0286]
[0287] Manufacturing of negative electrode slurry and battery production and evaluation
[0288] <Manufacturing of Negative Electrode Slurry>
[0289] Example 3-1
[0290] A slurry was prepared using a commercially available homodisperser (“Homodisperser 2.5 type” manufactured by PRIMIX Corporation). In a mayonnaise bottle (マヨネーズ bottle) as a container, 5.0 parts by mass of the aqueous solution of the binder for lithium ion batteries containing the hydrolyzed partial condensate (B) of the water-soluble polymer (A) and the amino-containing trialkoxysilane obtained in Example 1-1, 95 parts by mass of graphite with a D50 (median particle size) of 20 μm, 5 parts by mass of silicon monoxide particles with a D50 (median particle size) of 5 μm ("CC powder", manufactured by Osaka Chitanium Technology Co., Ltd.) and 1 part by mass of a conductive carbon additive (manufactured by Imelis Diesel Japan Co., Ltd., "Super C65") were mixed. Ion exchange water was added thereto so that the solid content concentration was 47%, and the container was set in the above-mentioned homogeneous disperser. Then, kneading was carried out at 2000 rpm for 30 minutes. Then, degassing was performed for 1 minute using a rotary and revolving mixer (manufactured by Shinky Co., Ltd., “Awatori Rentaro”) to obtain a negative electrode slurry.
[0291] For Example 3 and Comparative Example 3 other than Example 3-1, slurries were prepared in the same manner as in Example 3-1 except that the composition in Example 3-1 was changed as shown in the following table.
[0292] <Storage stability test of negative electrode slurry>
[0293] The storage stability of the slurry immediately after preparation was visually evaluated according to the following criteria.
[0294] A: The whole is a homogeneous paste with no liquid separation and no agglomerates.
[0295] B: The whole is in a substantially homogeneous paste state, slight liquid separation is observed, and no aggregates are observed.
[0296] C: A small amount of condensate and a large amount of liquid separation can be confirmed at the bottom of the container.
[0297] <Manufacturing of negative electrode>
[0298] The surface of the collector composed of copper foil was uniformly coated with the above-mentioned slurry for lithium ion batteries by doctor blade method in a manner that the film thickness after drying was 170 μm, dried at 80°C for 30 minutes, and then heated at 150°C / vacuum for 120 minutes. Then, the film (negative electrode active material layer) was pressed by roller press to a density of 1.5 g / cm 3 , thus obtaining a negative electrode.
[0299] <Manufacturing of positive electrode>
[0300] LiNi as the positive electrode active material 0.5 Co 0.2 Mn 0.3 O2, acetylene black as a conductive aid, and polyvinylidene fluoride (PVDF) as a binder are mixed in 88 parts by mass, 6 parts by mass, and 6 parts by mass, respectively, and the mixture is dispersed in an appropriate amount of N-methyl-2-pyrrolidone (NMP) to manufacture a positive electrode slurry for a lithium ion battery.
[0301] The positive electrode slurry for lithium ion battery was uniformly coated on the surface of the current collector composed of aluminum foil by a doctor blade method in a manner that the film thickness after drying was 110 μm, dried at 150°C for 30 minutes, and then heated at 150°C / vacuum for 120 minutes. Then, the film (positive electrode active material layer) was pressed by a roller press to a density of 3.0 g / cm 3 , thus obtaining the positive electrode.
[0302] <Evaluation of Electrode Flexibility>
[0303] The negative electrode was cut into pieces with a width of 10 mm and a length of 70 mm and wound on a diameter of 1 mm with the active material layer on the outside. The surface condition of the active material layer was observed on a Teflon (registered trademark) rod and evaluated according to the following criteria.
[0304] A: There is no cracking or peeling at all in the active material layer bonded to the current collector.
[0305] B: Cracks were found in the active material layer bonded to the current collector, but no peeling was observed.
[0306] C: Cracks were found in the active material layer bonded to the current collector, and peeling was also observed.
[0307] Electrodes with high electrode flexibility are less likely to cause problems such as curling, cracking, and loss of active material (undercutting) during the electrode manufacturing process. On the other hand, electrodes with low electrode flexibility are more likely to cause problems such as curling, cracking, and loss of active material during the electrode manufacturing process, which can easily become the main reason for the reduction in discharge capacity retention rate.
[0308] <Assembly of lithium half-cell>
[0309] In a glove box replaced with argon, the negative electrode and the positive electrode are punched into a material with a diameter of 16 mm and loaded on the inner side of the gasket on the Al lower cover of the test cell (manufactured by Japan Tomcell Co., Ltd.). Next, a diaphragm formed of a polypropylene porous film punched into a diameter of 24 mm (manufactured by CS TECH CO., LTD, product name "Selion P2010") is loaded, and after further injecting 500 μL of electrolyte to prevent air from entering, a commercially available metal lithium foil is punched into a material of 16 mm, and the outer packaging of the test cell is sealed with screws to assemble a lithium half-cell. The electrolyte used here is a solution in which LiPF6 is dissolved at a concentration of 1 mol / L in a solvent of ethylene carbonate / ethyl methyl carbonate = 1 / 1 (mass ratio).
[0310] <Charge and discharge measurement>
[0311] The lithium half-cell was placed in a thermostatic chamber at 25°C, and charging was started at a constant current (0.1C), and charging was completed (cut off) when the voltage reached 0.01 V. Next, discharging was started at a constant current (0.1C), and discharging was completed (cut off) when the voltage reached 1.0 V. This charging and discharging cycle was repeated 30 times.
[0312] In addition, under the above measurement conditions, "1C" means the current value at which a battery with a certain capacitance is discharged at a constant current within 1 hour. For example, "0.1C" means the current value at which the discharge is completed after 10 hours, and "10C" means the current value at which the discharge is completed after 0.1 hours.
[0313] <Discharge Capacity Retention Rate>
[0314] The discharge capacity retention rate was calculated by the following formula.
[0315] Discharge capacity retention rate = {(discharge capacity at the 30th cycle) / (discharge capacity at the 1st cycle)}×100 (%)
[0316] [Table 3]
[0317]
Claims
1. A binder aqueous solution for lithium ion batteries, the pH of the binder aqueous solution for lithium ion batteries being 5 to 8 and comprising: A water-soluble polymer (A) which is a polymer of a monomer group containing 20 mol% to 40 mol% of an unsaturated carboxylic acid or an inorganic salt thereof and 3 mol% to 40 mol% of a (meth)acrylamide group-containing compound relative to 100 mol% of the monomer group, and has a glass transition temperature of 110° C. or less; and A hydrolyzed partial condensate of an amino group-containing trialkoxysilane (B), The degree of condensation of the hydrolyzed partial condensate of the amino-containing trialkoxysilane (B) is 1.01 to 1000, The amino-containing trialkoxysilane is one or more selected from the group consisting of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2(aminoethyl)3-aminopropyltrimethoxysilane, N-2(aminoethyl)3-aminopropyltriethoxysilane and 3-triethoxysilyl-N-(1,3-dimethyl-butylene)propylamine.
2. The binder aqueous solution for lithium ion batteries according to claim 1, wherein The hydroxyalkyl (meth)acrylate having a hydroxyalkyl group having 2 to 4 carbon atoms is contained in an amount of 15 to 60 mol % based on 100 mol % of the monomer group.
3. The binder aqueous solution for lithium ion batteries according to claim 1 or 2, wherein The molar ratio of the amino group of the hydrolyzed partial condensate of the amino group-containing trialkoxysilane (B) to the carboxyl group of the water-soluble polymer (A), that is, amino group / carboxyl group, is 0.05 or more.
4. A negative electrode slurry for a lithium ion battery, wherein the pH of the negative electrode slurry for a lithium ion battery is 5 to 8 and comprises: A water-soluble polymer (A), wherein the water-soluble polymer (A) is a polymer of a monomer group containing 20 mol% to 40 mol% of an unsaturated carboxylic acid or an inorganic salt thereof and 3 mol% to 40 mol% of a (meth)acrylamide group-containing compound relative to 100 mol% of the monomer group, and has a glass transition temperature of 110° C. or less; A hydrolyzed partial condensate of an amino group-containing trialkoxysilane (B); A negative electrode active material (C); and Conductive carbon additive (D) having a zeta potential of 0 mV or more at pH 5 to 7, The degree of condensation of the hydrolyzed partial condensate of the amino-containing trialkoxysilane (B) is 1.01 to 1000, The amino-containing trialkoxysilane is one or more selected from the group consisting of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-2(aminoethyl)3-aminopropyltrimethoxysilane, N-2(aminoethyl)3-aminopropyltriethoxysilane and 3-triethoxysilyl-N-(1,3-dimethyl-butylene)propylamine. 5 . A negative electrode for a lithium ion battery obtained by applying the negative electrode slurry for a lithium ion battery according to claim 4 on a current collector and drying and solidifying the slurry.
6. A lithium ion battery comprising the negative electrode for a lithium ion battery according to claim 5.
Citation Information
Patent Citations
A signal distribution device
JP1984003761B2
Binder for lithium ion battery electrode, paste for lithium ion battery negative electrode using the same and manufacturing method of lithium ion battery negative electrode
JP2013089437A
Slurry for electricity storage device negative electrode and electricity storage device negative electrode, slurry for electricity storage device positive electrode and electricity storage device positive electrode, and electricity storage device
JP2015106488A
Binder composition for electricity storage device, slurry for electricity storage device, electricity storage device electrode, separator, and electricity storage device
JP2015118908A
Binder composition for lithium ion secondary battery, slurry composition for lithium ion secondary battery, method for manufacturing electrode for secondary battery, and lithium ion secondary battery
WO2015098507A1